2022
DOI: 10.1155/2022/6609752
|View full text |Cite
|
Sign up to set email alerts
|

Self-Consciousness, Self-Objectification, and Social Anxiety as Predictors of Photo Editing Behavior among Emerging Adults

Abstract: This study aims to assess the impact of self-consciousness, self-objectification, and social anxiety on photo editing behavior among emerging adults. Correlational research strategy was used for the present quantitative research, and convenient sampling strategy was used to collect data of 444 university students (135 males and 309 females) with the age range of 18-25 years. The self-consciousness scale, objectified body consciousness scale, photo manipulation scale, and social anxiety scale were used as asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Additionally, while the model shows a significant positive relationship between photo editing motivation and social appearance anxiety, no significant relationship was observed between social appearance anxiety and self-reflection. This is consistent with a study that previously indicated a positive relationship between social anxiety and photo editing behavior (Mustafa and Akram, 2022). According to Mowrer's (1951) two-factor theory, the relief from avoiding fears serves as a reinforcer, leading to subsequent resorting to avoidance as a solution in later encounters.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, while the model shows a significant positive relationship between photo editing motivation and social appearance anxiety, no significant relationship was observed between social appearance anxiety and self-reflection. This is consistent with a study that previously indicated a positive relationship between social anxiety and photo editing behavior (Mustafa and Akram, 2022). According to Mowrer's (1951) two-factor theory, the relief from avoiding fears serves as a reinforcer, leading to subsequent resorting to avoidance as a solution in later encounters.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, there are some ways in which humans could approve or disapprove others' behavior to communicate social acceptance, people seemed to have a strong tendency to transmit social evaluations and cues [41,42]. Conversely, people seem to adapt their behavior based on social cues (e.g., photo editing behavior) [43]. At the level of face-to-face interactions, one of the most cost-effective modes to convey these social signs and gathering information about other's actions, behaviors, and attitudes is through gossip, social status, reputation, and legitimacy dynamics [36,41,[44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to private self-awareness, we predicted a direct and negative link with men’s body dissatisfaction. Since private self-awareness implies a state of consciousness of one’s inner feelings, thoughts, and memories, it makes social factors (e.g., sociocultural standards of beauty) less accessible [ 37 ]. The more individuals focus on their internal states, the less they might perceive sociocultural pressures, thus experiencing lower body dissatisfaction ( Hypothesis 1b ).…”
Section: Introductionmentioning
confidence: 99%